The Image of Woman in The Novel Wa Nasitu Anni Imro’ah By Ihsan Abdul Quddus and Novel Kartini By Abidah El Khaileqy (Comparative Literature Study) - Kurnia, Ulfa; Tasnimah, Tatik Maryatut (Universitas Dian Nuswantoro, 2022)
This study aims to describe the comparison of the image of women in the novel Wa Nasitu Anni Imro'ah by Ihsan Abdul Quddus and the Novel Kartini by Abidah El Khaileqy (Comparative Literature Study). This type of research was qualitative with descriptive method. Qualitative research is research that intends to understand the phenomenon of what is experienced by research subjects such as actors, perceptions, motivations, and actions holistically and by way of description in the form of words and language, in a special natural context. The results of this study present some of the data obtained as research evidence, namely, the female image of the novel Wa Nasitu Anni Imro'ah by Ihsan Abdul Quddus and the Novel Kartini by Abidah El Khaileqy contained in this novel, namely: 1) personal image of women 2) image of women in the family, and 3) the image of women in society. The two novels show that women are capable and can become a highly educated person, have a career and get the same rights as men, without having to be limited by customary rules.